Learning, teaching, changing African archaeology - García Sánchez, Jesús; Revello Lami, Martina (Ex Novo: Journal of Archaeology, 2025)
Archaeology in Africa continues to be shaped by a long history of asymmetrical perspectives—colonial, Eurocentric, and post-colonial—that often reduce the continent to a passive recipient of outside interpretations. However, “Africa is various”, writes Kwame Anthony Appiah (1992) and Shepherd remembers one decade later (2002). Yet, as the contributions to this issue of Ex Novo demonstrate, African archaeologies are anything but static. They are dynamic fields of inquiry that interweave natural and cultural heritage, confront systemic challenges, and challenge entrenched stereotypes while generating new educational and social opportunities.